2003
DOI: 10.1074/jbc.m301293200
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-phosphate Dehydrogenase Modulates Vascular Endothelial Growth Factor-mediated Angiogenesis

Abstract: Glucose-6-phosphate dehydrogenase (G6PD), the first enzyme of the pentose phosphate pathway, is the principal intracellular source of NADPH. NADPH is utilized as a cofactor by vascular endothelial cell nitric-oxide synthase (eNOS) to generate nitric oxide (NO ⅐ ). To determine whether G6PD modulates NO ⅐ -mediated angiogenesis, we decreased G6PD expression in bovine aortic endothelial cells using an antisense oligodeoxynucleotide to G6PD or increased G6PD expression by adenoviral gene transfer, and we examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
131
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(144 citation statements)
references
References 29 publications
11
131
0
2
Order By: Relevance
“…Meanwhile, G6PD mut mice developed through ENU random mutagenesis with C3H mice are viable and display no apparent chronic hemolysis despite low G6PD activity (27). To date, G6PD mut mice have been studied for various pathological conditions such as sepsis, teratogenesis, cardiovascular diseases, myocardial dysfunction, and atherosclerosis (17,18,(20)(21)(22)(30)(31)(32)42,43). Because of their genetic background, C3H G6PD mut mice have some limitations for investigating obesity-mediated chronic inflammation and metabolic dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, G6PD mut mice developed through ENU random mutagenesis with C3H mice are viable and display no apparent chronic hemolysis despite low G6PD activity (27). To date, G6PD mut mice have been studied for various pathological conditions such as sepsis, teratogenesis, cardiovascular diseases, myocardial dysfunction, and atherosclerosis (17,18,(20)(21)(22)(30)(31)(32)42,43). Because of their genetic background, C3H G6PD mut mice have some limitations for investigating obesity-mediated chronic inflammation and metabolic dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased supply of NADPH, by limiting the regeneration of reduced glutathione, may magnify any level of oxidant stress occurring in diabetes. Additionally, if the observations made in cultured endothelial cells and in animals [3] apply to human G6PD deficiency, the decreased NADPH supply could affect eNOS activity, and thus reduce NO availability and endothelial performance. Of note, a facet of the impaired endothelial performance in in vitro and in vivo models of G6PD deficiency is an attenuated response to vascular endothelial growth factor and decreased angiogenesis [3].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, if the observations made in cultured endothelial cells and in animals [3] apply to human G6PD deficiency, the decreased NADPH supply could affect eNOS activity, and thus reduce NO availability and endothelial performance. Of note, a facet of the impaired endothelial performance in in vitro and in vivo models of G6PD deficiency is an attenuated response to vascular endothelial growth factor and decreased angiogenesis [3]. Our diabetic patients with G6PD deficiency showed that the endothelial cells of retinal vessels respond to angiogenic cues and form new vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Vitro Cell-network Formation Assay-The formation of network-like structures by HUVECs on Matrigel (BD Biosciences) was performed as previously described (31). The 12-well culture plates were coated with Matrigel according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%